1997
DOI: 10.1007/bf02436866
|View full text |Cite
|
Sign up to set email alerts
|

Densification of sol-gel thin films by ultraviolet and vacuum ultraviolet irradiations

Abstract: Abstract. Structural changes in SiO2 and TiO2 gel films were investigated using ultraviolet (UV) and vacuum ultraviolet (VUV) irradiations. A significant compaction with dehydration of SiO2 gel films was induced by irradiation of photons in the range of 9-18 eV. The refractive index and the shrinkage of the irradiated SiO2 gel films were comparable to those obtained by sintering at 1000~ Densification of TiO2 gel films was also observed with irradiation of 5-14 eV photons. However, effects of the irradiation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…For example, it has been reported that UV irradiation could increase the temperature of gel TiO 2 lms by less than 40 K. 27 Such an increase in temperature should however not be able to induce crystallization of the TiO 2 lm at room temperature. However, the present study is the rst demonstration of UV-induced crystallization of mesoporous materials.…”
Section: Methodsmentioning
confidence: 99%
“…For example, it has been reported that UV irradiation could increase the temperature of gel TiO 2 lms by less than 40 K. 27 Such an increase in temperature should however not be able to induce crystallization of the TiO 2 lm at room temperature. However, the present study is the rst demonstration of UV-induced crystallization of mesoporous materials.…”
Section: Methodsmentioning
confidence: 99%
“…Standard optical films of this material are widely used in aerospace applications. It is known from the literature [6][7][8][9] that the main effects of the UV irradiation on optical films are variations of thickness, chemical composition, structure, etc., all of them leading to changes in their optical properties. Bradford et al [6,8] found that the ultraviolet absorptance of silicon oxide films can be eliminated by UV irradiation and that the same UV treatment decreases their refractive index.…”
Section: Introductionmentioning
confidence: 99%
“…6) and led to a reduction in the Si-N-Si bonding angle. 29,30 In addition to analyzing film structure and measuring pore sizes, the porosity of the porous SiC x N y films generated after thermal annealing was quantified using XRR. Table I summarizes the pore morphology, porosity, and shrinkage results collected for the porous SiC x N y films.…”
Section: Ftir Analysis Of Sic X N Y /Porogen Hybrid and Porous Sic X N Ymentioning
confidence: 99%